A 'conservative' family? The Howard women and responses to religious change during the early Reformation, c.1530–15581. Issue 248 (4th March 2017) - Clark, Nicola
Abstract: The Howard family, dukes of Norfolk, are usually described as Catholics and considered to have been religiously 'conservative' throughout the early modern period and beyond. Thomas Howard, third duke of Norfolk, the family patriarch at the beginning of the Reformation, is thought to have remained on the conservative 'side' and it is assumed that the rest of the family followed his lead. By examining the responses of the Howard women to early religious change, this article argues that this was not the case; families did not react collectively but maintained relationships while occupying different positions across the shifting religious spectrum.